2018
DOI: 10.1002/bsd2.37
|View full text |Cite|
|
Sign up to set email alerts
|

Introducing a Sustainability Evaluation Framework based on the Sustainable Development Goals applied to Four Cases of South African Frugal Innovation

Abstract: Evaluating sustainability based on the Sustainable Development Goals (SDGs) is a complex but purposeful approach with a broad field of application. In order to handle the complexity of the SDGs and achieve flexibility at the same time, this paper introduces a three‐step evaluation system based on the SDGs for the assessment of the sustainability of innovations. It was used to assess four cases of South African frugal innovation with the conclusion that all four examined cases were sustainable, indicating an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…They have supported that the social engagement might create appropriate conditions for innovations to small‐ and medium‐sized enterprises, whereas multinational enterprises (MNEs) are driven more by institutional incentives to make innovations. Dressler and Bucher () have suggested an approach to examine the complexity of the UN_SDGs in the business world. They have developed a three‐step evaluation system in order to measure business sustainability innovation in relation to the implementation of the UN_SDGs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They have supported that the social engagement might create appropriate conditions for innovations to small‐ and medium‐sized enterprises, whereas multinational enterprises (MNEs) are driven more by institutional incentives to make innovations. Dressler and Bucher () have suggested an approach to examine the complexity of the UN_SDGs in the business world. They have developed a three‐step evaluation system in order to measure business sustainability innovation in relation to the implementation of the UN_SDGs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, Arnold [8] analyzed 50 different frugal innovations with their contributions to SDGs and further confirmed that frugal innovation was a major driver of SDGs implementation. Dressler and Bucher [30] proposed and applied a framework on an African case context to express the links between SDGs and frugal innovation. Some studies focused on one or two dimensions of sustainability with frugal innovation perspectives.…”
Section: A Frugal Innovation and Sustainabilitymentioning
confidence: 99%
“…Bebbington and Unerman (2018) and Stafford‐Smith et al (2017) stress that the SDGs are also important in the accounting field. SDGs have the potential to inform and influence accounting practices and sustainability reporting (Bebbington, Russell, & Thomson, 2017) and represent an attractive invitation to act in favour of sustainability (Dressler & Bucher, 2018; Shoaf, Jermakowicz, & Epstein, 2018; Thorlakson, de Zegher, & Lambin, 2018; Verdolini, Bak, Ruet, & Venkatachalam, 2018). However, in their study of 2,413 sustainability reports, Rosati & Faria, 2019a, 2019b highlight a relatively low number of references to the SDGs contained within them.…”
Section: Literature Review Of Sdgs and Businessmentioning
confidence: 99%